2010
DOI: 10.4314/ijbcs.v3i5.51061
|View full text |Cite
|
Sign up to set email alerts
|

Cooking as a source of indoor air pollution in rural areas of Tanzania

Abstract: This study was concerned with the assessment of the contribution of cooking fuelwood, charcoal and kerosene to indoor air pollution in households in Msangani, Chahua and Kazimzumbwi villages in the Coast Region, Tanzania. It has also assessed the performance of Single Compartment Model in predicting indoor pollution levels under Tanzania conditions. The methods used in this study were household survey, measurements, and observation. The pollutants measured were Carbon monoxide (CO), Sulphur dioxide (SO 2 ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
2
Order By: Relevance
“…For this occupation, the number of men are higher than that of women as many men engage in fish frying. This is different from findings from other cross sectional studies conducted in different parts of the world which reported biomass smoke exposure to women and mothers who are more responsible in cooking practices at homes [ 33 – 35 ] while in the process of fish frying in Tanzania men are more exposed to air pollution from burning of firewood as an occupational exposure. Other studies have also reported high exposure of biomass smoke to women as they are responsible for cooking at home at their early age and hence cumulative exposure over time which lead to early manifestation of the disease [ 32 ].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…For this occupation, the number of men are higher than that of women as many men engage in fish frying. This is different from findings from other cross sectional studies conducted in different parts of the world which reported biomass smoke exposure to women and mothers who are more responsible in cooking practices at homes [ 33 – 35 ] while in the process of fish frying in Tanzania men are more exposed to air pollution from burning of firewood as an occupational exposure. Other studies have also reported high exposure of biomass smoke to women as they are responsible for cooking at home at their early age and hence cumulative exposure over time which lead to early manifestation of the disease [ 32 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Findings from this study indicate that biomass use is still common in occupational settings including fish frying working environment. Health risks associated with this have been documented in many studies [ 13 , 18 , 21 , 33 , 45 , 49 ] hence there is a need for immediate action to protect this workforce.…”
Section: Discussionmentioning
confidence: 99%
“…For this occupational exposure, men are more exposed than women as women who fry sh are too few. This is different from ndings from a other cross sectional studies conducted in different parts of the world which reported exposure to women and mothers who are more responsible in cooking practices at homes [23][24][25] while in the process of sh frying in Tanzania men are more exposed to air pollution from burning of rewood as an occupational exposure. Other studies have also reported high exposure of biomass smoke to women as they are responsible for cooking at home at their early age and hence cumulative exposure over time which lead to early manifestation of the disease Almost all sh vendors reported having respiratory symptoms (cough, breathlessness, wheezing and sputum production) interfere with their daily activities in one way or another.…”
Section: Discussioncontrasting
confidence: 80%
“…Findings from this study indicate that biomass use is still common in occupational settings including sh frying working environment. Health risks associated with this have been documented in many studies [9,12,14,23,35,37] hence there is a need for immediate action to protect this workforce.…”
Section: Discussionmentioning
confidence: 99%